2021
DOI: 10.1159/000515336
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ventilation-Perfusion Single-Photon Emission Computed Tomography to Select the Target Lobe for Endobronchial Valve Lung Volume Reduction

Abstract: <b><i>Background:</i></b> Quantitative planar ventilation-perfusion (VQ) has a complementary role in target lobe selection for endobronchial valve lung volume reduction (EBV-LVR), especially in homogenous disease. We investigated a novel method of lung lobar quantitation using VQ single-photon emission computed tomography (SPECT) with computed tomography (CT) to generate a parameter called the ventilation-perfusion differential index (VQDI). <b><i>Aim:</i></b> Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…This study evaluated the lobar perfusion algorithm relative to zonal perfusion and found that the former was not inferior to the standard of care imaging conducted by the zonal perfusion as previously demonstrated in other studies (Gao et al, 2020;Provost et al, 2017;Singh et al, 2020;Tee et al, 2021). It is important to note that zonal perfusion still has clinical merit as apical lung quantification is better characterized using the zonal perfusion algorithm of the upper lobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated the lobar perfusion algorithm relative to zonal perfusion and found that the former was not inferior to the standard of care imaging conducted by the zonal perfusion as previously demonstrated in other studies (Gao et al, 2020;Provost et al, 2017;Singh et al, 2020;Tee et al, 2021). It is important to note that zonal perfusion still has clinical merit as apical lung quantification is better characterized using the zonal perfusion algorithm of the upper lobes.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally quantitative lung perfusion was performed utilizing planar imaging with molecular imaging processing software dividing the lungs into upper, middle and lower zones and analyzing counts obtained from each zone as opposed to anatomical lobar anatomy. With the increased use of SPECT/CT and development of CT‐based fissure‐identifying artificial intelligence algorithms, quantification perfusion studies can now be performed with lobar analysis with small studies showing enhanced quantification of the perfusion in a 5‐lobar analysis (Gao et al, 2020; Provost et al, 2017; Singh et al, 2020; Tee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We set out in this study to define the role of nuclear medicine, particularly quantitative lobar SPECT/CT, in BLVR therapy. Prior trials have shown the utility of SPECT/CT when there are multiple candidate target lobes, particularly in cases of homogenous or mild heterogenous emphysema [16]. Therefore, the objective is to define the role of SPECT/CT in cases of homogenously affected emphysematous lungs in which high-resolution CT (HRCT) could not identify a single suitable target lobe.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the objective is to define the role of SPECT/CT in cases of homogenously affected emphysematous lungs in which high-resolution CT (HRCT) could not identify a single suitable target lobe. Prior studies such as Tee et al [16] and Kristiansen et al [17] have investigated SPECT/CT's role in BLVR planning with preliminary results showing its utility in a small sample size [17]. Tee et al [16] investigated a mixed distribution of homogenous and heterogenous emphysema.…”
Section: Introductionmentioning
confidence: 99%
“…9 While ELVR with EBV has been performed in Australia since 2007, local evidence has been, until recently, focussed on mechanisms of action and assessment criteria. [10][11][12] However, there have now been two recent studies published with local data utilising accepted international guidelines for selection, which allows us to examine the local experience. The first by Sidhu et al 13 was a retrospective consecutive review of 39 patients undergoing ELVR with EBV at two Victorian centres.…”
mentioning
confidence: 99%